The farming and husbandry of Colossoma macropomum: From Amazonian waters to sustainable production - Hilsdorf, Alexandre Wagner Silva; Hallerman, Eric; Valladão, Gustavo Moraes Ramos; Zaminhan-Hassemer, Micheli; Hashimoto, Diogo Teruo; Dairiki, Jony Koji [UNESP]; Takahashi, Leonardo Susumu [UNESP]; Albergaria, Francielly Corrêa; Gomes, Maria Emília de Sousa; Venturieri, Rossana Luiza Leite; Moreira, Renata Guimarães; Cyrino, José Eurico Possebon (Wiley, 2022)
Within the rich diversity of South American freshwater fish, Colossoma macropomum (Characiformes: Serrasalmidae), known as tambaqui, cachama or blackfin pacu, can reach 30 kg, is a traditional product in regional fish markets and has drawn the attention of fish farmers since the 1930s. Considerable progress achieved in different fields of aquaculture science has contributed to the growth of tambaqui production. Tambaqui has proven suitable for both monoculture and polyculture systems, and for both extensive and intensive production systems aimed at achieving sustainable, higher productivity with minimal environmental impact. Studies of the reproductive anatomy and physiology of the species proved fundamental to development of techniques to boost commercial production, contributing to development of protocols for hormonally induced spawning and artificial propagation in the 1970s. Newly hatched larvae must be fed with live foods until they can be weaned to artificial feeds at about 100 mg weight. Despite its importance for aquaculture, only a few studies have reported components of quantitative genetic variance and parameters for weight at age, morphometric traits and disease resistance. Genomic tools currently available can be applied to detect variation relevant to performance and to accelerate the process of genetic improvement. While the species’ feeding habit allows the use of diets containing 75%–85% plant protein, much more work needs to be done to optimize aquafeeds. Refinement of tambaqui production methods has the potential to significantly boost South American aquaculture. We recommend research on diets, genetic improvement and system optimization to spur further productivity and achieve sustainable tambaqui culture.
Keywords: aquaculture; cachama; Characiformes; cultivation; gamitana; tambaqui